The Social Economy in Rural Korea and the Policy Direction - 김정섭 (농촌지역 사회적 경제 실태와 활성화 방안, 2016)
There is a growing interest in the social economy, which has been amplified along with legislative enactment and policy implementation related to social economy organizations such as the Framework Act on Cooperatives. Increasing even in rural areas, social economy organizations are expanding their position. There is a vigorous movement in such a way that local residents address current issues by organizing cooperatives. In terms of responding to issues various sectors in rural areas are facing, the social economy can play an important role. In that it is a problem-solving strategy based on the residents' autonomy and initiative, its value and potential can be highly valued. Promotion of the social economy should follow precise diagnosis of its actual conditions. It is not an easy task to put into practice the principles of the social economy based on the residents' initiative and solidarity. However, in the long-term perspective, it can be a great help to prepare a foundation for the social economy in solving various problems that rural areas are facing. This research examines the actual condition of social economy organizations in rural areas in general. It also attempts to analyze the network among social economy organizations and the related governance.